2005
DOI: 10.1007/s00412-005-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

The JIL-1 kinase regulates the structure of Drosophila polytene chromosomes

Abstract: The JIL-1 kinase localizes to interband regions of Drosophila polytene chromosomes and phosphorylates histone H3 Ser10. Analysis of JIL-1 hypomorphic alleles demonstrated that reduced levels of JIL-1 protein lead to global changes in polytene chromatin structure. Here we have performed a detailed ultrastructural and cytological analysis of the defects in JIL-1 mutant chromosomes. We show that all autosomes and the female X chromosome are similarly affected, whereas the defects in the male X chromosome are qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
83
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 26 publications
(48 reference statements)
5
83
0
Order By: Relevance
“…The GFP-lacI transgenic stock 128.1, and the lac operator repeats transgenic stock 4D5 were the generous gifts of Dr L. Wallrath (University of Iowa, Iowa City). The application of the GFP-lacI and lac operator repeat stocks for X chromosome identification in JIL-1 mutant backgrounds is described by Deng et al (Deng et al, 2005).…”
Section: Drosophila Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The GFP-lacI transgenic stock 128.1, and the lac operator repeats transgenic stock 4D5 were the generous gifts of Dr L. Wallrath (University of Iowa, Iowa City). The application of the GFP-lacI and lac operator repeat stocks for X chromosome identification in JIL-1 mutant backgrounds is described by Deng et al (Deng et al, 2005).…”
Section: Drosophila Stocksmentioning
confidence: 99%
“…The GFP-lacI transgenic stock 128.1, and the lac operator repeats transgenic stock 4D5 were the generous gifts of Dr L. Wallrath (University of Iowa, Iowa City). The application of the GFP-lacI and lac operator repeat stocks for X chromosome identification in JIL-1 mutant backgrounds is described by Deng et al (Deng et al, 2005)./TM3 Sb Ser stocks were obtained from the Bloomington Stock Center, whereas the Su(var)3-9 1 and Su(var)3-9 2 stocks were from the Umeå Stock Center. The molecular lesion of Su(var)3-1 3 was determined by PCR mapping and sequencing, as described by Zhang et al (Zhang et al, 2003).…”
mentioning
confidence: 99%
“…
ABSTRACT In this study, we show that the haplo-enhancer effect of JIL-1 has the ability to counterbalance the haplo-suppressor effect of both Su(var)3-9 and Su(var)2-5 on position-effect variegation, providing evidence that a finely tuned balance between the levels of JIL-1 and the major heterochromatin components contributes to the regulation of gene expression.T HE essential JIL-1 histone H3S10 kinase (Jin et al 1999;Wang et al 2001) is a major regulator of chromatin structure (Deng et al 2005(Deng et al , 2008) that functions to maintain euchromatic domains while counteracting heterochromatization and gene silencing (Ebert et al 2004;Lerach et al 2006;Zhang et al 2006;Bao et al 2007). In the absence of the JIL-1 kinase, the major heterochromatin markers H3K9me2, HP1a [Su(var)2-5], and Su(var)3-7 spread to ectopic locations on the chromosome arms Deng et al 2007Deng et al , 2010.
…”
mentioning
confidence: 99%
“…Transgenes inserted into centromeric regions of chromosomes in Drosophila can exhibit position-effect variegation (PEV), a mosaic silencing of transcription of euchromatic genes as a result of their placement in or near heterochromatin (reviewed by Wallrath 1998;Henikoff 2000;Schotta et al 2003;Girton and Johansen 2007). It has recently been demonstrated that alleles of the JIL-1 locus are important regulators of chromatin structure and gene expression (Wang et al 2001;Ebert et al 2004;Deng et al 2005;Lerach et al 2005Lerach et al , 2006. The JIL-1 histone H3S10 tandem kinase localizes specifically to euchromatic interband regions of polytene chromosomes in Drosophila ( Jin et al 1999) and analysis of a JIL-1 null allele, JIL-1 z2 , has shown that JIL-1 is essential for viability (Wang et al 2001;Zhang et al 2003).…”
mentioning
confidence: 99%